Rhinovirus species/genotypes and interferon-λ: subtypes, receptor and polymorphisms – missing pieces of the puzzle of childhood asthma?. Issue 3 (30th March 2017) - Bergauer, Annika; Sopel, Nina; Kroß, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al.
The correspondence from C. Scagnolari and co-workers raises some interesting points that we could not address in a single manuscript, but were otherwise addressed in our Predicta study and will therefore be reported on in future. Analysis of systemic IFN-lambda, during asthma exacerbations, should complement IFN analysis in the airways http://ow.ly/DkhV309HL6e